THE ALGORITHM OF OPERATION PERFORMING OF DIVIDING THE NUMBER BY TWO IN THE SYSTEM OF RESIDUAL CLASSES - Poliskyi, Yu. D. (Science and Transport Progress, 2007)
The method of solving problem of division on two for numbers in residue class system are observed. The method is algorithmically simple and not complicated to scheme realization for making of effective computing's structures.